Mast Cell Degranulation Decreases Lipopolysaccharide-Induced Aortic Gene Expression and Systemic Levels of Interleukin-6 In Vivo. (24th October 2019) - Springer, Jason M.; Raveendran, Vineesh V.; Zhang, Mingcai; Funk, Ryan; Smith, Donald D.; Maz, Mehrdad; Dileepan, Kottarappat N.
Abstract : Mast cells play an important role in immunomodulation and in the maintenance of vascular integrity. Interleukin-6 (IL-6) is one of the key biomarkers and therapeutic target in systemic vasculitis. The objective of the current study is to describe the role of mast cells in arterial IL-6 homeostasis. Eight- to ten-week-old male C57BL/6 (wild-type) mice were injected with either (a) saline, (b) compound 48/80 (a systemic mast cell degranulating agent), (c) lipopolysaccharide (LPS), or (d) a combination of C48/80 and LPS. Twenty-four hours after the injections, mice were sacrificed and serum samples and aortic tissues were analyzed for determining inflammatory response and cytokine expression profile. The results revealed that induction of mast cell degranulation significantly lowers serum IL-6 levels and aortic expression of IL-6 in LPS-treated mice. Significantly higher aortic expression of toll-like receptor-2 (TLR-2) and TNF- α was seen in the LPS and LPS+C48/80 groups of mice compared to controls. Aortic expression of TLR-4 was significantly decreased in LPS+C48/80 compared to C48/80 alone. LPS+C48/80-treated mice presented with a 3-fold higher aortic expression of suppressor of cytokine signaling (SOCS-1) compared to saline-injected groups. The inhibition of LPS-induced increase in serum IL-6 levels by mast cell degranulation was not seen in H1R knockout mice which suggests that mast cell-derived histamine acting through H1R may participate in the regulatory process. To examine whether the mast cell-mediated downregulation of LPS-induced IL-6 production is transient or cumulative in nature, wild-type mice were injected serially over a period of 10 days (5 injections) and serum cytokine levels were quantified. We found no significant differences in serum IL-6 levels between any of the groups. While mice injected with C48/80 or LPS had higher IL-10 compared to vehicle-injected mice, there was no difference between C48/80- and LPS+C48/80-injected mice. In conclusion, in an in vivo setting, mast cells appear to partially and transiently regulate systemic IL-6 homeostasis. This effect may be regulated through increased systemic IL-10 and/or aortic overexpression of SOCS-1.